2014
DOI: 10.1017/s1368980014001682
|View full text |Cite
|
Sign up to set email alerts
|

The development of a composition database of gluten-free products

Abstract: Objective: To develop a composition database of a number of foods representative of different categories of gluten-free products in the Italian diet. Design: The database was built using the nutritional composition of the products, taking into consideration both the composition of the ingredients and the nutritional information reported on the product label. Setting: The nutrient composition of each ingredient was obtained from two Italian databases (European Institute of Oncology and the National Institute fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 16 publications
7
51
0
1
Order By: Relevance
“…In order to fill this gap, we built a composition database of a number of foods representing the main sources of intake of GF products in the Italian diet. In particular, we estimated the nutritional composition of 60 GF products taking into consideration both the ingredient composition and the nutritional information reported on the product label . Although the nutritional composition data of GF products were estimated and not directly analysed, our data suggested that, regarding the estimated micronutrient values of the GF foods considered, several differences with respect to the conventional foods can be pointed out, especially for breads and pasta.…”
Section: Macro‐ and Micronutrient Content Of Gf Productssupporting
confidence: 90%
“…In order to fill this gap, we built a composition database of a number of foods representing the main sources of intake of GF products in the Italian diet. In particular, we estimated the nutritional composition of 60 GF products taking into consideration both the ingredient composition and the nutritional information reported on the product label . Although the nutritional composition data of GF products were estimated and not directly analysed, our data suggested that, regarding the estimated micronutrient values of the GF foods considered, several differences with respect to the conventional foods can be pointed out, especially for breads and pasta.…”
Section: Macro‐ and Micronutrient Content Of Gf Productssupporting
confidence: 90%
“…Gluten-free cookies and some sweet products at the Italian market have more than 20% of fat, and 7.5% of them are saturated fat [34]. In addition, gluten-free products contain less vitamins and minerals and frequently have lower protein content than the wheat-containing food products.…”
Section: Nutrition Quality Of the Gluten-free Dietmentioning
confidence: 99%
“…Formerly, Mazzeo et al [34] published a food composition database including 60 gluten-free food representatives of diferent categories sold on the Italian market (more than 50% of them are distributed all over Europe). Almost all the gluten-free products were high in available carbohydrates, with approximately 50% of sugar content in cookies, breakfast and sweet products, which results in a high glycaemic load when consumed.…”
Section: Nutrition Quality Of the Gluten-free Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…ingredients from such cereals where gluten is removed, such as bread, cookies, pasta, etc. [76]. The diet and the GF products are often low in B vitamins, calcium, vitamin D, zinc, iron, magnesium, and fibre.…”
Section: Sex and Gender Differences In Healthmentioning
confidence: 99%